INFLUENCE OF TEMPERATURE FLUCTUATION ON THERMOPHILIC ANAEROBIC DIGESTION OF MUNICIPAL ORGANIC WASTE (Journal of Engineering, 2008)
A laboratory-scale experiment was carried out to estimate the influence of temperature fluctuation on thermophilic anaerobic digestion of municipal organic waste (MOW). Heating failure was simulated by decreasing temperature gradually from 55 °C to 20 °C gradually 2 h time need for temperature decrease and recovery. Under conditions of 8.0 g/ (L·d) and 15 d respectively for MOW load and retention time. Following results were found: (1) biogas production almost stopped and VFA (Volatile Fatty Acid) accumulated rapidly when accompanied by pH decrease. (2) With low temperature (20°C) duration of 1, 5, 12 and 24 h, the thermophilic anaerobic digestion system reproduce methane after temperature fluctuation of 3, 11, 56 and 72 h. (3) The bacteria was influenced by the temperature fluctuation where it decayed, hydrolysis, acidification was high as the low temperature interval lasted. (4) The thermophilic  microorganisms were highly flexible to temperature fluctuation.